FARMER SURVIVAL MECHANISM DURING THE PANDEMIC: A CASE STUDY OF THE TENGGER TRIBAL COMMUNITY, EAST JAVA - Hoiril Sabariman; Anik Susanti (Jurnal Sosiologi Reflektif, 2022)
The Covid-19 pandemic has had a multidimensional impact on the community, especially the vulnerable, namely smallholder farmers in Indonesia. Currently, the challenges farmers face are not limited to land ownership, seasonality, erosion, price factors, marketing networks, and the quality of agricultural products. However, it is also disturbed to meet basic needs, resulting in decreased welfare. This study aims to uncover and analyze the mechanism of farmer survival and welfare improvement carried out by Tengger Tribe smallholders in the Bromo mountains, Probolinggo Regency. The case study method was used to explain the mechanism of improving the welfare of smallholder farmers. The research informants were determined based on specific considerations and criteria: six farmers based on land area ownership and crop type—data collection with observations, interviews, and field notes. The findings of this study show that there are several survival mechanisms during a pandemic. First, smallholder farmers with narrow land do not always depend on agricultural products but also diversify their jobs such as entrepreneurship, improving social marketing networks, and supporting services for tourism activities in Gunung Bromo. Second, the mechanism for enhancing welfare carried out by smallholder farmers is intensification by increasing production and reducing consumption. Farmers deploy production factors such as labor, capital, intercropping planting methods, and the use of manure. Meanwhile, reducing the consumption of smallholder farmers in the Tengger Tribe limits the most basic types of food goods to reduce shopping in the market to only a few types of essential goods. Through these rational choices,  smallholder farmers in the  Tengger Tribe were able to survive the storm of the  Covid-19 Pandemic.Pandemi Covid-19 memiliki dampak multidimensional bagi masyarakat, khususnya kaum rentan yaitu petani gurem di Indonesia. Saat ini tantangan yang dihadapi petani tidak sebatas pada faktor kepemilikan lahan, musim, erosi, faktor harga, jaringan pemasaran dan kualitas hasil pertanian. Namun, guna memenuhi kebutuhan dasar juga mengalami gangguan, sehingga kesejahteraan yang menurun. Tujuan penelitian ini untuk mengungkap dan menganalisis mekanisme survival petani dan  peningkatan kesejahteraan yang dilakukan oleh petani gurem Suku Tengger di pegunungan Bromo Kabupaten Probolinggo. Metode studi kasus dipilih untuk menjelaskan mekasime peningkatan kesejahteraan petani gurem. Informan penelitian ditentukan berdasarkan pertimbangan dan kriteria tertentu yaitu enam petani yang didasakan kepemilikan luas lahan dan jenis tanaman. Pengumpulan data dengan observasi, wawancara dan catatan lapangan. Temuan penelitian ini menunjukkan bahwa terdapat beberapa mekanisme survival di masa pandemi. Pertama, petani gurem dengan lahan sempit tidak selalu menggantungkan pada hasil pertanian, tetapi juga melakukan diversifikasi pekerjaan seperti wirausaha, meningkatkan jaringan sosial pemasaran, serta jasa pendukung kegiatan pariwisata di Gunung Bromo. Kedua, mekanisme peningkatan kesejahteraan yang dilakukan petani gurem adalah intensifikasi dengan cara memperbesar produksi dan mengurangi konsumsi. Petani mengerahkan faktor produksi seperti, tenaga kerja, modal, metode tanam tumpang sari, dan penggunaan pupuk kandang. Sementara itu, cara mengurangi konsumsi petani gurem di Suku Tengger membatasi jenis-jenis barang makanan yang paling pokok, sehingga mampu menekan belanja di pasar sampai pada beberapa jenis barang esensial saja. Melalui pilihan-pilihan rasional ini, petani gurem di Suku Tengger mampu bertahan dari badai Pandemi Covid-19.